2015
DOI: 10.5751/es-07283-200204
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the role of universities in addressing sustainability challenges: the Mitchell Center for Sustainability Solutions as an institutional experiment

Abstract: ABSTRACT. As the magnitude, complexity, and urgency of many sustainability problems increase, there is a growing need for universities to contribute more effectively to problem solving. Drawing upon prior research on social-ecological systems, knowledgeaction connections, and organizational innovation, we developed an integrated conceptual framework for strengthening the capacity of universities to help society understand and respond to a wide range of sustainability challenges. Based on experiences gained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 40 publications
0
43
0
Order By: Relevance
“…; Hart et al . ). For that project, collaborators relied on rhetoric to prepare team members for a series of Maine Public Broadcasting documentaries about the teams’ science, developing science communication workshops informed by rhetorical theory that helped teams develop and refine messages that audiences could identify with.…”
Section: Promoting Shared Meaning and Identificationmentioning
confidence: 97%
See 1 more Smart Citation
“…; Hart et al . ). For that project, collaborators relied on rhetoric to prepare team members for a series of Maine Public Broadcasting documentaries about the teams’ science, developing science communication workshops informed by rhetorical theory that helped teams develop and refine messages that audiences could identify with.…”
Section: Promoting Shared Meaning and Identificationmentioning
confidence: 97%
“…Connection and collaboration are key areas of attention for rhetorical training, as rhetoric-based initiatives work to promote shared meaning and identifi cation between speakers or writers and audiences. The University of Maine (UMaine) utilized this capacity in its Sustainability Solutions Initiative, a statewide network of sustainability science teams, including more than 100 faculty hailing from over 20 disciplines across the social and biophysical sciences, representing 11 institutions of higher education, and funded by a $20 million NSF grant in 2009 ( Figure 2 ; Whitmer et al 2010 ;Hart et al 2015 ). For that project, collaborators relied on rhetoric to prepare team members for a series of Maine Public Broadcasting documentaries about the teams' science, developing science communication workshops informed by rhetorical theory that helped teams develop and refi ne messages that audiences could identify with.…”
Section:  Promoting Shared Meaning and Identificationmentioning
confidence: 99%
“…There may be historical disparities between disciplines to contend with, such as differences in relative size (in terms of numbers of persons, instrumentation, and funding) and investigative style (especially in the treatment of qualitative information). Staying within disciplinary silos during training does not help with bridging these gaps (Hart et al, 2015). Finally, project durations of only 2-3 years long are too short for trust-building within groups and several boundary settings have been created recently at IUEM to stimulate such interactions.…”
Section: The Humanities Enter the Gamementioning
confidence: 99%
“…Indeed, despite some very interesting success stories, it is important to acknowledge that in many places there are numerous barriers against interdisciplinary and participatory science. For example, Hart et al (2015) discussed how the role of universities could be strengthened to address sustainability challenges, by requiring strong institutional changes regarding both how research and training are organized in order to overcome "disciplinary silos." "Disciplinary silos" is a figurative term referring to how the one-discipline/one-department structure of most higher education institutions reinforces and rewards single-discipline researchers and impedes inter-or transdisciplinary initiatives and careers.…”
Section: Introductionmentioning
confidence: 99%
“…For faculty who want to make a difference by contributing to the development of solutions, it is immediately apparent that the resources of several disciplines must be mobilized and coordinated. We have found that these faculty are often willing to do the extra work required to build collaborative capacity (Hart et al, 2015), and programs like ours are creating novel mechanisms to support their efforts.…”
Section: Introductionmentioning
confidence: 97%